On a class of Riemannian manifolds with harmonic Weyl conformal curvature tensor - Witold Roter (Annales Universitatis Paedagogicae Cracoviensis: Studia Mathematica, 2004)
The paper deals with the local structure of those $n$-dimensional $(ngeq 5)$ Riemannian manifolds of harmonic conformal curvature $(M,g)$ which are not conformally flat and admit a non-homothetic conformal change of metric $g mapstoar g$ such that $(M,ar g)$ is locally symmetric.